2018
DOI: 10.1101/378133
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Functional cross-talk between allosteric effects of activating and inhibiting ligands underlies PKM2 regulation

Abstract: Allosteric regulation is central to the role of the glycolytic enzyme pyruvate kinase M2 (PKM2) in cellular metabolism. Multiple activating and inhibitory allosteric ligands regulate PKM2 activity by controlling the equilibrium between high activity tetramers and low activity dimers and monomers. However, it remains elusive how allosteric inputs upon simultaneous binding of different ligands are integrated to regulate PKM2 activity. Here, we show that, in the presence of the allosteric inhibitor L-phenylalanin… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
6
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 91 publications
2
6
1
Order By: Relevance
“…An activity‐based determination of FBP activation of refolded PKM2 protein yielded an AC 50 value of ~ 2 μ m (Fig. D), which is also comparable to previously reported values for PKM2 activation and binding of FBP to nonphosphorylated PKL , although somewhat higher than a more recently reported AC 50 of 118 n m . Despite the kinetic behavior of the refolded PKM2 in response to FBP being more consistent with past studies, Prep 2 was laborious and we sought an alternative preparation of native, bacterially expressed PKM2 that is largely free of bacterial FBP.…”
Section: Resultssupporting
confidence: 85%
See 4 more Smart Citations
“…An activity‐based determination of FBP activation of refolded PKM2 protein yielded an AC 50 value of ~ 2 μ m (Fig. D), which is also comparable to previously reported values for PKM2 activation and binding of FBP to nonphosphorylated PKL , although somewhat higher than a more recently reported AC 50 of 118 n m . Despite the kinetic behavior of the refolded PKM2 in response to FBP being more consistent with past studies, Prep 2 was laborious and we sought an alternative preparation of native, bacterially expressed PKM2 that is largely free of bacterial FBP.…”
Section: Resultssupporting
confidence: 85%
“…A). These results suggested that most of the enzyme was already bound to FBP from the bacteria despite purification as previously reported . Independent preparations of PKM2 using this approach occasionally produced enzyme that showed some FBP activation; however, this variability in FBP activation complicated detailed kinetic analysis.…”
Section: Resultssupporting
confidence: 75%
See 3 more Smart Citations